Structural quantification of multi-thick hard roof and strong ground pressure control in large mining height stope: a case study - Yangbo Lu; Shaohong Yan; Kunyou Zhou; Chenxi Zhang; Yi Zhou (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract The mining of deep large-height longwall faces leads to frequent occurrences of strong ground pressure, at the same time, there are multi-thick hard rock strata in the roof of the longwall face, therefore, it is important to master the fracture quantification characteristics of multi-thick hard roof in large mining height stope for control of strong ground pressure. This study takes the 30202 longwall face of Muduchaideng Coal Mine as the case study. Based on the structure characteristics of multi-thick hard rock strata, which obtained by numerical simulation experiment, the fracture mechanical mechanism of multi-thick hard roof under different structures was obtained. Through numerical simulation experiment and microseismic monitoring data, it is obtained that the roof range that produce stress on the longwall face support is the key strata III and underlying rock strata, and the fracture parameters of multi-thick hard roof were obtained by the mechanical model of overhanging fracture of thick hard rock strata and the structural quantification model of multi-thick hard rock roof of 30202 longwall face is established, combined with microseismic monitoring data, the energy evolution law of multi-thick hard roof fracture was obtained and the method of long-hole hydraulic fracturing of thick hard rock strata was proposed to control of strong ground pressure, in which make the phenomenon of strong ground pressure is obviously reduced.